2017
DOI: 10.1093/mmy/myx125
|View full text |Cite
|
Sign up to set email alerts
|

A novel, tomographic imaging probe for rapid diagnosis of fungal keratitis

Abstract: Fungal keratitis is a leading cause of ocular morbidity and blindness in developing countries. Diagnosing fungal keratitis currently relies on a comparative evaluation of corneal biopsy or scraping using a direct microscopy and culture results. These methods not only carry the risk of developing complications due to the invasive tissue sampling but also are largely limited by diagnostic speed and accuracy, making it difficult to initiate timely appropriate antifungal therapy. Therefore, rapid and noninvasive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…Correct diagnosis of fungal infections can be problematic, however recently imaging-based tools were developed to accurately diagnose infections such as fungal keratitis. Based on the structure of caspofungin a chemical probe exhibiting high affinity to Aspergillus and possibly also other fungal pathogens was developed which could serve as a basis for development of an imaging system 307 .…”
Section: Methods For Monitoring In Vivo Performancmentioning
confidence: 99%
“…Correct diagnosis of fungal infections can be problematic, however recently imaging-based tools were developed to accurately diagnose infections such as fungal keratitis. Based on the structure of caspofungin a chemical probe exhibiting high affinity to Aspergillus and possibly also other fungal pathogens was developed which could serve as a basis for development of an imaging system 307 .…”
Section: Methods For Monitoring In Vivo Performancmentioning
confidence: 99%
“…Thus, wildlife animals are recognized as environmental reservoir for many human and animal infections [32, 33]. In Korea, a few studies have reported the molecular detection of E. bieneusi in livestock [34, 35] and in bats [36]; however, the infection burden of this microsporidian fungal pathogen in wildlife is largely unknown. Therefore, in the present study, the prevalence and genotypes of this parasite in wild animal populations in Korea were determined.…”
Section: Introductionmentioning
confidence: 99%
“…At 24 h post-intrastromal injection of Aspergillus conidia, animals were anesthetized, and the probe was applied topically to the corneal ulcer. Within 5 min of the application, a fluorescent signal was detectable and quantifiable with an in vivo confocal microscopy; the signal disappeared at 60 min of application [47]. Thus, this method allows for the prospective assessment of fungal burden in the same animal, similar to the fluorescent reporter strain approach.…”
Section: Disease Assessmentmentioning
confidence: 96%
“…Then, a 33G Hamilton syringe is inserted into the tunnel to deliver a 1-2 µL inoculum directly into the underlying stroma. Regardless of fungal species, 10 5 total conidia is commonly used inoculum, although this can vary by a log-fold either way [1,32,[47][48][49][50][51][52].…”
Section: Intrastromal Injectionmentioning
confidence: 99%